ANTIHYPERURICEMIA SCREENING OF Mimosa pudica L. HERB EXTRACT THROUGH ITS ANALGESICS AND ANTIINFLAMMATORY ACTIVITY ASSAY - Sumiwi, S.A -; Susilawati_Y -; Muhtadi, A -; Abdassah, M -; Subarnas, A - (Bionatura, 2014)
Traditionally, herbs of Mimosa pudica L. are being usedto treat insomnia, hematuria, inflammation, emesis,dismenorrhoea, menorrhagia, arthritis rhematoid, convultion,depresion, and diabetes. Previous in vitro studyshowed that herbs extract of Mimosa pudica L inhibiteduric acid formation via xanthine oxidase inhibition of82.11 and 62.10% for concentration of 125 and 62.5 μg/mL, respectively. Hyperuricemia is indicated by pain andoedema which are the symptoms of inflammation. This invivo study was perfor-med to screen antihyperuricemiaactivity of herbs extract of Mimosa pudica L throughanalgesic and antiinflammatory assays on mice.Analgesic activity of Mimosa pudica L herb extract atdosage of 125, 250 and 500 mg/kg of body weight wasobserved on mice using writhing reflex method withacetic acid 0,07 % as inducer. The results showed thatall three dosages inhibited pain at the percentage of9.58, 45.35, and 60.28% respectively. Antiinflammatoryactivity assay was done using carageenan-induced pawedema method on white male rats. Dosages used were250, 500 and 1000 mg/kg of body weight. The resultsshowed that all three dosages inhibited edema at thepercentages of 35.20, 42.74, and 51.10% respectively. It isconcluded that herbs extract of Mimosa pudica L can beproposed as an antihyperuricemia.Keywords: Antihyperuricemia, Analgesic, Anti-inflammatory,Mimosa pudica L.